2021
DOI: 10.3892/mmr.2021.12317
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of targeted sequencing of BRCA1 and BRCA2 in a cohort of breast cancer families: New insight into pathogenic variants in patients and at‑risk relatives

Abstract: Breast cancer (Bc) is the most commonly diagnosed cancer worldwide and a major health concern in egypt. There is a known association between pathogenic variants identified in breast cancer susceptibility gene (BRCA)1 and 2 and the risk of developing Bc. However, the number of studies investigating mutations in BRCA1 and BRCA2 in egypt remains limited. Thus, the aim of the present study was to investigate the frequency of BRCA1 and BRCA2 variants in patients with Bc and their relatives. For this purpose, 11 fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…This intriguing ethnic diversity indicates Egypt's unique genetic composition, situated as a transcontinental nation between the northeastern corner of Africa and the southwestern corner of Asia. Notably, previous research corroborates these findings, as the identified BRCA1 (c.4900A > G, c.2612C > T, c.3548A > G, 0.3113A > G) and BRCA2 (c.7397 T > C, c.1114A > C) clusters were observed in an earlier Egyptian study [ 67 ] as well as within Arab African populations like Algerian [ 68 ], Bahrainian [ 69 ], Moroccan [ 70 ] and Tunisian [ 71 ] groups, alongside Asian populations encompassing Chinese [ 72 ], Korean [ 73 ], Iranian [ 74 ] and Indian [ 75 ] cohorts, and even in American and European populations such as Brazilian [ 76 ], and Italian [ 77 ] ones, respectively. This reinforces the intricate interplay of various ethnic backgrounds shaping the genetic landscape of Egypt.…”
Section: Discussionsupporting
confidence: 79%
“…This intriguing ethnic diversity indicates Egypt's unique genetic composition, situated as a transcontinental nation between the northeastern corner of Africa and the southwestern corner of Asia. Notably, previous research corroborates these findings, as the identified BRCA1 (c.4900A > G, c.2612C > T, c.3548A > G, 0.3113A > G) and BRCA2 (c.7397 T > C, c.1114A > C) clusters were observed in an earlier Egyptian study [ 67 ] as well as within Arab African populations like Algerian [ 68 ], Bahrainian [ 69 ], Moroccan [ 70 ] and Tunisian [ 71 ] groups, alongside Asian populations encompassing Chinese [ 72 ], Korean [ 73 ], Iranian [ 74 ] and Indian [ 75 ] cohorts, and even in American and European populations such as Brazilian [ 76 ], and Italian [ 77 ] ones, respectively. This reinforces the intricate interplay of various ethnic backgrounds shaping the genetic landscape of Egypt.…”
Section: Discussionsupporting
confidence: 79%
“…Few relevant studies have been conducted to address the frequency of germline mutations in familial Egyptian BC patients, and they were only to investigate BRCA1/2 germline profiling. For example, a recent study by Saied et al investigated the frequency of BRCA1/2 variants in patients with BC and their relatives [21]. Another study by , used whole exome sequencing to investigate genetic predisposition in five Egyptian families with BC.…”
Section: Discussionmentioning
confidence: 99%
“…Since the advent of next-generation sequencing (NGS), multi-gene testing panels have been increasingly applied to detect genetic mutations that may be associated with increased BC risk [20]. However, very limited studies have addressed the frequency of germline mutations in BC susceptibility genes among Egyptian patients with BC family history, such as Saied et al [21] and Kim et al [22]. Thus, in the current study and to the best of our knowledge, we were the first to assess the frequency of deleterious germline mutations in familial BC Egyptian patients using a multi-gene panel sequencing of 93 genes, to better understand the contribution of the inherited germline mutations in the predisposition of BC in an Egyptian BC cohort selected for BC family history.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent study, using NGS, we found that among 113 patients, 18 (15.9%) harbored germline BRCA mutations [ 17 ]. Furthermore, recurrent mutations have been reported in the North African population, such as BRCA2 -c.1310_1313delAAGA [ 17 , 18 , 19 , 20 ]. However, some mutations are likely to be specific to the Tunisian population and more precisely to patients from the North-East, such as BRCA1 -c.211dupA [ 13 , 14 , 15 , 21 ], or from the South, such as the BRCA1 -c.5030_5033delCTAA and the BRCA2 -c.17_20 delAAGA mutations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%